Analytical Study Of Inclusivity In Design Of University Campuses In Lahore - Madiha Ghafoor , Muhammad Taimur Sarwar , Saira Naeem , Rabia Ahmad Qureshi (Migration Letters, 2024)
Inclusion of people with disabilities in mainstream society of Pakistan is a crucial target that has widely been overlooked. It is now worldwide believed that the exclusion of these people from main social and physical setup is not only because of their disability but because the physical infrastructure does not allow them to participate. One reliable way to bring them into mainstream society is to equip them with quality education. For that matter physical infrastructure of educational institutes should be efficient to accommodate the needs of such user groups satisfactorily. The aim of this exploratory research was to audit the university campuses in Lahore to assess the quality of built environment based upon principles of acce[1]ssibility and inclusivity, and to identify the physical barriers that impede independent accessibility of people. For this purpose, an inclusivity assessment tool was developed specifically for the architectural context of Lahore, Pakistan. The study of the four sample universities in this research clearly identifies the deficiencies in design for inclusivity making it possible for designers to propose design solutions.